Respuesta :
Complete Question:
The coordinate grid below shows triangle ABC and its image after translation, triangle A'B'C': Triangles ABC and A' B' C' are shown.
[tex]A = (-6, 10)[/tex]
[tex]B = (-7, 7).[/tex]
[tex]C = (-4, 6).[/tex]
[tex]A' = (2, 7).[/tex]
[tex]B' = (1, 4).[/tex]
[tex]C' = (4, 3).[/tex]
Which of the following completes the rule for this translation,
(x, y) → (x + 8, ___)?
Answer:
y - 3
Step-by-step explanation:
Given
See Complete Question
Required
Complete the rule of translation
Taking A and A' as a point of reference
[tex]A = (-6, 10)[/tex] and [tex]A' = (2, 7).[/tex]
By comparing the x coordinates of A and A'
[tex]-6 + k = 2[/tex]
Make k the subject
[tex]k = 2 + 6[/tex]
[tex]k = 8[/tex]
So, the x coordinate is translated by x + 8
Similarly,
By comparing the y coordinates of A and A'
[tex]10 + k = 7[/tex]
Make k the subject
[tex]k= 7 - 10[/tex]
[tex]k = -3[/tex]
So, the y coordinate is translated by y - 3
Hence, the complete translation is: (x + 8, y - 3)